How Does Corporate Governance Affect Bank Capitalization Strategies? - Anginer, Deniz (World Bank, Washington, DC, 2014)
This paper examines how corporate governance and executive compensation affected bank capitalization strategies for an international sample of banks in 2003-2011. "Good" corporate governance, which favors shareholder interests, is found to give rise to lower bank capitalization. Boards of intermediate size, separation of the chief executive officer and chairman roles, and an absence of anti-takeover provisions, in particular, lead to low bank capitalization. However, executive options and stock wealth invested in the bank are associated with better capitalization except just before the crisis in 2006. In that year, stock options wealth was associated with lower capitalization, which suggests that potential gains from taking on more bank risk outweighed the prospect of additional loss. Banks' tendencies to continue payouts to shareholders after experiencing negative income shocks are shown to reflect executive risk-taking incentives.